Postharvest Quality Improvement of Bell Pepper (Capsicum annuum L. cv Nagano) with Forced-Air Precooling and Modified Atmosphere Packaging - Yeboah, Samuel; Hong, Sae Jin; Park, Yeri; Choi, Jeong Hee; Eum, Hyang Lan (MDPI AG, 2023)
Optimum postharvest storage conditions increase the postharvest quality and shelf life of horticultural crops. The effects of forced-air precooling (FAP) and modified atmosphere packaging (MAP) on shelf life, physicochemical quality, and health-promoting properties of bell pepper (Capsicum annuum L. cv. Nagano) harvested at 90 and 50% coloring stages in May and July respectively, stored at 11 degrees C, 95% relative humidity were assessed. Fruits were subjected to four treatments: FAP + 30 mu m polyethylene liner (FOLO); FAP-only (FOLX); 30 mu m polyethylene liner-only (FXLO); and control (FXLX). The quality attributes, viz. weight loss, firmness, color, soluble solids content (SSC), soluble sugars, total phenolic content (TPC), total flavonoid content (TFC), 2,2-dephenyl-1-picrylhydrazyl (DPPH), and 2,2 '-azino-bis-3-ethylbenzo-thiazoline-6-sulfonic acid (ABTS) were evaluated. The investigated parameters differed significantly (p < 0.05) among treatments except for soluble sugars. FOLO maintained sensory quality (weight loss, firmness, and color), physicochemical (SSC and soluble sugars), and health-promoting properties compared to other treatments during storage. The 50% coloring fruits had a huge variation between treatments than 90% coloring. The results revealed more TPC and antioxidant capacity in the 50% than in the 90% coloring fruits. The study highlights the need to consider the ideal fruit coloring stage at harvest under the effect of FAP and MAP treatments in preserving bell pepper's postharvest quality and shelf life.